PENGARUH BUDAYA ORGANISASI DAN KEPUASAN KERJA TERHADAPPRODUKTIVITAS KERJA KARYAWAN - K JATMIKO, BENEDIKTUS (Jurnal Ilmu Manajemen (JIM), 2013)
Productivity is influenced by many factors, such as jobsatisfaction and organizational culture. The purpose of this research wasto determine the effect of organizational culture and job satisfaction onemployee productivity, either partially or simultaneously. The sampleused in this study 50 employees of the production at PT. Rock StoneUniverse. Measurement scale using a Tribox method, continued validity,reliability and the classical assumptions for testing data. Hypothesistesting using multiple linear regression analysis with SPSS. Based onthe research result there is no significant influence of organizationalculture variables partially on employee productivity, And the significantinfluence on job satisfaction variable on employee productivityKeywords : organizational culture, job satisfaction, and productivity.